(untitled) (Biodiversitas Journal of Biological Diversity, 2016)
The aim of the research was to find out palms species diversity in Mioswaar Island, Teluk Wondama Regency, West Irian Jaya (Papua). The research result indicated that the forest of Mioswaar Island had been 3 sub families of palms, i.e. Arecoideae, Calamoideae, and Coryphoideae, consist of 12 genera, namely: Areca, Arenga, Calamus, Caliprocalix, Caryota, Gronophyllum, Gulubia, Licuala, Orania, Metroxylon, Pigafetta, and Pinanga. The most common species palm was Arenga microcarpa, Gulubia costata, and Gronophyllum pinangoides. In this island, palms grew at 2-200 asl. Â© 2005 Jurusan Biologi FMIPA UNS Surakarta Key words: inventory, diversity, description, palm species, Mioswaar island.